Turn Sequence and Classroom Discourse: IRF and its Role in Language learning - Jasim, Nagham Oudeh; Khalif, Reem Zead (Journal of Educational and Psychological Sciences, 2022)
Classroom discourse is considered an important aspect of learning and teaching the new language. The turn sequence is one type of classroom discourse and it’s considered as an important way to learn the skill of speaking the English Language, and one type of classroom discourse is the (IRF) pattern. IRF pattern is an abbreviation for (teacher initiation, students’ response, and feedback or follow up by (teacher or student). This research focuses on discussing classroom discourse and the (IRF) pattern as an important way to discover the role of it in learning the English Language. It also focuses on the teacher’s role, as the dominant power of discourse inside the classroom and how to use the (IRF) pattern to encourage students to participate in different activities inside their classes. Data were collected from a regular English Language Learning classroom, and then the data were transcribed and analyzed to show how the (IRF) pattern was used in the classroom. The results showed that the use of turn sequence and the IRF pattern was very useful to stimulate and encourage students and learners of English Language to participate by talking about different things inside the classroom either between their teacher and themselves or between the students but by the help of the teacher.